Mitral valve replacement in dogs using pig aortic valve heterografts - Hamilton, David I. (1968)
Mitral valve replacement using pig aortic valve heterografts has been performed in 27 dogs, siting the grafts in the `atrial position'. Buffered acid formaldehyde sterilization offered the advantages that it is simple and, by de-naturing the proteins of the graft, may minimize `rejection' phenomena. It may offer some self-sterilizing property to the graft within the host post-operatively. The question whether heterograft valves will ultimately calcify remains unanswered. The aortic valve has been shown to function satisfactorily in place of the mitral valve for up to four months, producing normal haemodynamic studies. The `atrial position' of the graft has the advantage that the left ventricular cavity becomes totally available for its pumping activities. The fate of these animals depended upon developing mitral incompetence around the grafts and thrombus, leading to mitral stenosis, rather than to rejection phenomena. The operation described requires accuracy in orientating the graft. Mounting heterografts (with almost the whole of the aortic wall cut away) in a Dacron-covered metal frame pre-operatively provided a valve in a range of sizes which can be inserted in the same manner as any prosthesis in current use. Methods of sterilization and storage and the ultimate fate of heterografts in vivo require further study. Failure such as calcification will probably not develop suddenly. Such a valve could be replaced if necessary. The continued investigation and clinical use of heterografts appears to be justified when viewed against the uncertain outcome of the other methods of valve replacement.